Results of the Study the Content of Amprolium in Meat, Eggs, Organs and Tissues in Chickens - Nasimov Shukhrat Naimovich (Researchparks Publishing, 2021)
The article presents the results of experimental studies to determine the content of the residual amount of the drug (substances) of amprolium in meat, eggs, organs and tissues of chickens that received the drug with feed in various dosages. At the same time, it was found that after the use of the drug with the substance of amprolium, even in the recommended doses, there are restrictions on poultry products for human consumption.